Impact of video-assisted thoracic surgery versus open thoracotomy on postoperative wound infections in lung cancer patients: A systematic review - Helvy Susanti (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Lung cancer remains a leading cause of cancer-related mortality worldwide, with surgical resection being the primary curative approach for early-stage non-small cell lung cancer. Postoperative wound infections following thoracic surgery significantly impact patient outcomes, healthcare resources, and quality of life. Purpose: To evaluate the incidence, risk factors, management, and outcomes of postoperative wound infections comparing Video-Assisted Thoracic Surgery (VATS) versus open thoracotomy in lung cancer patients. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Adult patients with diagnosed lung cancer who underwent surgical resection, I: Video-Assisted Thoracic Surgery (VATS), C: Open thoracotomy, O: Incidence of postoperative wound infections, infection severity, causative microorganisms, time to infection development, treatment approaches, and impact on hospital stay, S: Randomized controlled trials. The article search was conducted systematically using the keywords: "Video-Assisted Thoracic Surgery,” AND "VATS," AND "Open Thoracotomy," AND "Lung Cancer," AND "Pulmonary Carcinoma," AND "Surgical Site Infection," AND "Wound Infection," AND "Postoperative Complications," AND "Surgical Wound Dehiscence," AND "Surgical Outcomes," AND "Minimally Invasive Surgery". Results: The analysis showed that VATS had lower overall complication rates, reduced mortality, and shorter hospital stays compared to open thoracotomy, especially in high-risk patients like those with obesity. VATS conversion to thoracotomy significantly increased complications and mortality. Robot-assisted thoracic surgery offered additional benefits, including less blood loss and lower conversion rates than conventional VATS. Conclusion: VATS is preferred over open thoracotomy for lung cancer due to lower complications, mortality, and shorter hospital stays. Conversion to thoracotomy increases risks. Robotic surgery offers additional benefits but at higher costs. Overall, minimally invasive approaches reduce wound-related complications.